Transient Analysis on Multiphase Transmission Line Above Lossy Ground Combining Vector Fitting Technique in ATP Tool - Colqui, Jaimis Sajid Leon; Araujo, Anderson Ricardo Justo de; Pascoalato, Taina Fernanda Garbelim [UNESP]; Kurokawa, Sergio [UNESP]; Pissolato Filho, Jose (Ieee-inst Electrical Electronics Engineers Inc, 2022)
Several approaches to calculate the ground-return impedance and admittance matrices are proposed in the literature. Carson's approach assumes a lossy ground modeled by frequency-independent conductivity where displacement currents and non-perfectly conducting ground effects are neglected. However, Nakagawa's approach considers both characteristics and also the frequency-dependent (ED) soil electrical parameters that can be incorporated into his formulations. This paper investigates the influence of Nakagawa's approach and Carson's approach on the transient responses using the ATP tool. First, the performances of the Bode's method and Vector Fitting (VF) technique for approximating the characteristic impedance Z(c)(s) and propagation H(s) are also investigated for the JMarti's line model. Then, lightning-induced voltages (LIVs) developed for a lightning striking at the shield wire of an overhead transmission line (OHTL) on a high-resistive Ell soil are investigated. Results demonstrated a much higher accuracy using the VF for approximating Z(c)(s) and H(s) than Bode's method. Transient voltages on the OHTL calculated with Nakagawa's approach showed notable differences compared to those obtained with Carson's approach. The voltage peaks are reduced when Nakagawa's approach is utilized, especially when transmission lines are located on high-resistive soils.
Keywords: Electromagnetic transient analysis; Transmission lines; Lightning-induced voltages; Rational fitting techniques; Frequency-dependent soil electrical parameters